Comparison of the volumetric composition of lamellar bone and the woven bone of calluses. (July 2018) - Martínez-Reina, Javier; García-Rodríguez, Javier; Mora-Macías, Juan; Domínguez, Jaime; Reina-Romo, Esther
Woven tissue is mainly present in the bone callus, formed very rapidly either after a fracture or in distraction processes. This high formation speed is probably responsible for its disorganized microstructure and this, in turn, for its low stiffness. Nonetheless, the singular volumetric composition of this tissue may also play a key role in its mechanical properties. The volumetric composition of woven tissue extracted from the bone transport callus of sheep was investigated and compared with that of the lamellar tissue extracted from the cortical shell of the same bone. Significant differences were found in the mineral and water contents, but they can be due to the different ages of both tissues, which affects the mineral/water ratio. However, the content in organic phase remains more or less constant throughout the mineralization process and has proven to be a good variable to measure the different composition of both tissues, being that content significantly higher in woven tissue. This may be linked to the abnormally high concentration of osteocytes in this tissue, which is likely a consequence of the more abundant presence of osteoblasts secreting osteoid and burying other osteoblasts, which then differentiate into osteocytes. This would explain the high formation rate of woven tissue, useful to recover the short-term stability of the bone. Nonetheless, the more abundant presence of organic phase prevents the woven tissue from reaching a stiffness similar to that of lamellar tissue in the long term, when it is fully mineralized.